O tratamento da variação linguística no material Aprender Sempre - Rigon, Rafaela (Universidade Federal de São Carlos, 2023)
The present work addresses linguistic variation in the educational context, specifically focusing on the didactic material Aprender Sempre. Linguistic variation is a natural phenomenon in languages, reflecting social, regional, and cultural differences. This study analyzes how two sequences of activities from the mentioned material, one from the 6th grade and another from the 7th grade of secondary education, address this phenomenon, because, as according to guidelines from the Base Nacional Comum Curricular (BRASIL, 2017) and the Currículo Paulista (SÃO PAULO, 2019), they should promote a more inclusive and linguistically sensitive education. To achieve this, we draw upon the pedagogy of linguistic variation (BORTONI-RICARDO, 2004, 2005; BAGNO, 2007; ZILLES; FARACO, 2015) and conduct a documentary analysis, detailing the selected sequences based on ten criteria adapted from Bagno (2007). Through this research, we aim to provide a critical analysis of the treatment of variation in a material that, according to the São Paulo State Department of Education, is intended for content recovery and deepening. Furthermore, we emphasize the relevance of including activities in these materials that genuinely consider respect and valorization of different forms of expression.
The treatment of linguistic variation in the teaching material Aprender Sempre
Keywords: Pedagogia da variação linguística; Ensino de língua portuguesa; Análise documental; Pedagogy of linguistic variation; Portuguese language teaching; Documentary analysis; LINGUISTICA, LETRAS E ARTES::LETRAS; LINGUISTICA, LETRAS E ARTES::LINGUISTICA; LINGUISTICA, LETRAS E ARTES